Comparison of neutralization power of amendment based on calcium and magnesium in soils of flat pampas of Santa Fe - Carrizo, María Eugenia; Alesso, Carlos Agustín; Billoud, Hernán; Pilatti, Miguel Ángel (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The objective of this study was to compare the neutralization power of amendments based on calcium and magnesium and to assess their effects on the cation exchange complex in soils of flat Pampas of Santa Fe. Three amendments (lime, dolomite and mixture amendment) at rates calculated to neutralize 100% and 150% of exchangeable hydrogen were applied to samples from soils incubated for 60 days. The responses on actual and potential pH, and hydrogen, calcium and magnesium exchangeables were assessed. The increment of actual pH showed differences between amendments and the order of response was lime > dolomite > mixture amendment. No difference between the applied rates were observed. The potential pH was more sensitive to the type and of rates amendment. All treatments reduced the level of unsaturation, although the full neutralization was not achieved with the tested rates. Increments of exchangeable calcium were observed in all treatments and the greatest calcium saturation was obtained when lime or mixture amendment were applied at the highest rate. Dolomite and mixture amendment significantly increased the content of magnesium regardless of the rate. The information presented here is useful for prescribing magnesic-calcareous amendments in soils of the flat Pampas of Santa Fe.